The Risk Factors for Perioperative Serum Albumin Variation in Pediatric Patients Undergoing Major Gastroenterology Surgery - Liu, Qingshuang; Gao, Kai; Zheng, Chao; Guo, Chunbao (Frontiers in Surgery, 2021)
Background: The albumin, a negative acute-phase protein, is important for perioperative morbidity, even in patients with normal preoperative levels. This study intend to determine the perioperative factors related with the postoperative reduction in serum albumin (ΔALB) and its influence on perioperative outcome in a pediatric general surgical cohort. Methods: This single-center retrospective review included 939 pediatric patients who underwent major gastroenterology surgery from August 2010 to August 2019. The patients were dichotomized into a high ΔALB group (≥14.6%) and a low ΔALB group (<14.6%) based on the mean value of ΔALB (14.6%). the independent risk factors for ΔALB, were explored using the propensity score matching to minimize potential selection bias and subjected to method multivariable logistic regression model. Furthermore, in 366 matched patients, the influences of operating time on perioperative outcomes were analyzed. Results: Among the 996 patients reviewed, 939 patient records were enrolled in the final analysis. Controlling for other factors, multivariable analysis showed that a high CRP on POD 3 or 4 [odds ratio (OR) = 2.36 (95% CI, 1.51–3.86); p = 0.007], a longer operating time [OR = 1.18 (95% CI, 1.00–1.53); p = 0.014), and the presence of Charcot's triad [OR = 1.73 (95% CI, 1.05–2.83); p = 0.031] were factors that predicted a high ΔALB level. A high ΔALB level was also related with gastrointestinal functional recovery delay, reflected by the postoperative defecation (p = 0.013) and bowel movement (p = 0.019) delay and the high occurrence of postoperative complications (16.1 vs. 10.9%, OR, 1.57; 95% CI, 1.02–2.41, P = 0.0026). Conclusions: The high ΔALB level was correlated with postoperative outcome. To obtain a safe recovery and discharge after a major abdominal operation, the above risk factors for ΔALB could be addressed in the perioperative period.